Design of Pin Diode Detector - Md Yunus, Nurul Amziah (2001)
A good light detector is when it could convert all the photon to the electrical signal in high speed. The junction photodetector is the most common photodetection device. Nowadays, the known photodetectors are the PN diode, the PIN diode and the APD diode. At one time PN diodes were the most common detection device used in lightwave system. Now the PIN diodes become the most prevalent devices used in photodetector. The PIN diode is an acronym for positive-intrinsic-negative diode. It is a photodiode with a large neutrally doped intrinsic region sandwiched between p-doped and n-doped semiconducting regions. PIN diode is a unique device. It is a semiconductor device that operates as a variable resistor at RF and microwave frequencies and as a good detector in optical communication. In this project, the homojunction PIN device, has been selected, which consists of GaAs material. GaAs is a good material in designing the optoelectronic infrared photodetector devices. To design an optimal PIN diode detector, a study of the variation intrinsic region widths, doping concentrations, reverse biasing voltages and the photon flux is carried out. By studying these variations, it has lead to the determination of the best possible design of the photo detector, to produce the maximum photocurrent at the output. To observe the optimization, the Medici Avant! is used as a device simulation software. This software is preferred because it is cheaper and faster technique to discover the properties and characteristic of PIN diode detector. In Medici, a model of two-dimensional (2D) PIN diode for the electrical (without illumination) and optical (with illumination) was performed. In the simulation, the total thickness of the diode is originally set to be 3.0 um length with the intrinsic region is 1.5 um thick. In evaluating the PIN photodiode performance, a uniform optical generation is made to take place in a 1.5 um thick region located in the middle of the intrinsic region. A light pulse with 1 ps duration was focused on the depletion region of the diode. Subsequently, details simulations were performed to find the 1-V characteristics, the photocurrent response and the output pulse width of the GaAs PIN detector. The results from the simulation qualitatively demonstrate that the PIN diode could be used as the photodetector. This is because it could produce high current at minimum intrinsic region width, optimally to 0.5 um, with low-doped intrinsic region, which is 5E15 cm-3 and simultaneously at high reverse biasing voltage best to be 35 V and at large number of photon flux density, 5E21 photonlsec/cm2•